ROSES are Read, STEEP are Green: Mapping Sustainability Indicators Across Lifecycle Stages in EV Battery Production Through a Systematic Review - Arumbinang, Nimas Ayu; Garniwa, Iwa; Koestoer, Raldi Hendrotoro Seputro; Aritenang, Wendy (Automotive Experiences, 2024)
The rapid expansion of the electric vehicle (EV) market presents a paradox: while increasing production and lowering costs are essential for widespread adoption, these efforts also intensify the environmental and social impacts, particularly in lithium-ion (Li-ion) battery production. Comprehensive sustainability assessments are needed across all stages of battery production. This review employed the ROSES framework to analyze 40 Scopus-indexed research papers systematically. Extracted indicators are categorized by the STEEP (Sociocultural, Technological, Economic, Environmental, and Political-Legal) dimensions. The dual approach identifies critical sustainability gaps and examines the interplay between these dimensions. By mapping each indicator to a specific lifecycle stage—ranging from raw material extraction to end-of-life disposal—the review highlights critical stages for improving sustainability in EV battery production. The study uncovers complex relationships between sustainability factors and establishes a comprehensive framework to address these challenges. As a result, it provides policymakers, industry leaders, and researchers with a solid foundation for developing informed strategies to enhance the sustainability of EV battery production.